Analysis of Metal in Wastewater Collected from Three Pharmaceutical Industries Located in Tongi Area of Gazipur District - Islam, Shakibul; Alam, AKM< Rashidul; Islam, Shahidul (Bangladesh Journal of Scientific and Industrial Research, 2010)
Wastewater qualities of three pharmaceutical industries were determined during July 2005 to January 2006. Alkaline earth metals including calcium (Ca) and magnesium (Mg) of wastewater ranged 41.79-54.5mgL-1 and 10.5996-32.2926 mgL-1, respectively. Alkali metals including potassium (K) and sodium (Na) of wastewater ranged 3.44-18.98 mgL-1 and 67.57- 128.71 mgL-1, respectively. Transition metal iron (Fe) ranged 1.02-2.13 mgL-1. On an average metals including zinc (Zn), lead (Pb), nickel (Ni) and cadmium (Cd) were in trace amount i.e. 84.32 μ gL-1, 11.59 μ gL-1, 4.96 μ gL-1 and 0.1047 μ gL-1, respectively in the wastewater. Copper (Cu) was undetected in wastewater. The average amount of iron of site N, magnesium of site S and potassium of site B of wastewater were higher than that of the standard of Department of Environment (DoE) of Bangladesh. Key words: Metals; Pharmaceutical wastewater; DoE standards. DOI: 10.3329/bjsir.v45i3.6538 Bangladesh J. Sci. Ind. Res. 45(3), 277-282, 2010